An evaluation of clonal relationship by PFGE method in Acinetobacter baumannii isolates, examining integron presence and antibiotic resistance - Öner, Sedef Zeliha; Er, Hatice; Çalışkan, Ahmet; Demir, Melek; Şenol, Hande; Kaleli, İlknur (The Journal of Infection in Developing Countries, 2024)
Introduction: This study aims to investigate the presence of class 1, 2, and 3 integrons in Acinetobacter baumannii isolates, evaluate the relationship between integrons and antibiotic resistance and determine the clonal relationship between isolates by PFGE method. Methodology: A total of 188 A. baumannii strains between February 2020 and March 2023 were included in the study. The antibiotic susceptibility was assessed per the recommendations of “The European Committee on Antimicrobial Susceptibility Testing”. Integrons have been identified by polymerase chain reaction. The clonal relationship between isolates was evaluated with PFGE. Results: Integron carriage was observed in 45.7% of isolates. Of these, 44.1% carried class 0.5% carried class 2, and 2 (1.1%) carried both classes of integrons. Among the integron positive isolates, the rate of only class 1 integron was 96.5% (83/86), the rate of only class 2 was 1.2% (1/86), and the rate of only two integron classes together was 2.3% (2/86). In the presence of class 1 integrons, the MDR and XDR phenotypes were found to be high (p = 0.005, p = 0.029). PFGE method detected 26 clusters and 177 pulsotypes on the dendrogram. When the clusters are evaluated separately within themselves, in all of the isolates in the Y and Z clusters (100%), class 1 integron positivity was observed in cluster A at 52.2%, cluster J at 42.1%, and cluster N at 22.2%. Conclusions: Class 1 integron positivity observed in all of the isolates in the two clusters suggests the likelihood of clonal transfer alongside the horizontal transfer.